SISTEM INFORMASI ADMINISTRASI PERNIKAHAN - Prakasiwi, Degita Astari (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2017)
Office Business Religion (KUA) is one of society service center which giving service for society especially marriage registration. At KUA Sumay, the process of marriage registration has used a computerization but the use of computer is not maximal. It cause the data at this KUA become unorganized. Every organization need a good system to process every data into information and so this KUA. To make the data more organized, it is a necessity to design a new system. This new system expected to resolve the problem. So this research aim to design a new system of data processing. The methods used to support this research are observation, interview, library research, and laboratory research. The result of this research is an application which later can have a better system in organizing the data. The application built by using visual basic 6.0 and MySQL as its database.